Drought-responsive WRKY transcription factor genes TaWRKY1 and TaWRKY33 from wheat confer drought and/or heat resistance in Arabidopsis - He, Guan-Hua (BMC Plant Biol, 2016)
BACKGROUND: Drought stress is one of the major causes of crop loss. WRKY transcription factors, as one of the largest transcription factor families, play important roles in regulation of many plant processes, including drought stress response. However, far less information is available on drought-responsive WRKY genes in wheat (Triticum aestivum L.), one of the three staple food crops. RESULTS: Forty eight putative drought-induced WRKY genes were identified from a comparison between de novo transcriptome sequencing data of wheat without or with drought treatment. TaWRKY1 and TaWRKY33 from WRKY Groups III and II, respectively, were selected for further investigation. Subcellular localization assays revealed that TaWRKY1 and TaWRKY33 were localized in the nuclei in wheat mesophyll protoplasts. Various abiotic stress-related cis-acting elements were observed in the promoters of TaWRKY1 and TaWRKY33. Quantitative real-time PCR (qRT-PCR) analysis showed that TaWRKY1 was slightly up-regulated by high-temperature and abscisic acid (ABA), and down-regulated by low-temperature. TaWRKY33 was involved in high responses to high-temperature, low-temperature, ABA and jasmonic acid methylester (MeJA). Overexpression of TaWRKY1 and TaWRKY33 activated several stress-related downstream genes, increased germination rates, and promoted root growth in Arabidopsis under various stresses. TaWRKY33 transgenic Arabidopsis lines showed lower rates of water loss than TaWRKY1 transgenic Arabidopsis lines and wild type plants during dehydration. Most importantly, TaWRKY33 transgenic lines exhibited enhanced tolerance to heat stress. CONCLUSIONS: The functional roles highlight the importance of WRKYs in stress response. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-016-0806-4) contains supplementary material, which is available to authorized users.